Knowledge of Diabetes among Diabetic Patients Attending at Tertiary Level Hospital - Shrestha, Krishna Devi; KC, Takma; Ghimire, Rachana (Journal of Nursing Education of Nepal, 2022)
Background: The prevalence of Diabetes Mellitus is growing at an alarming rate across the globe. Obtaining knowledge regarding diabetes is the initial step in formulating a prevention program for diabetes which can assist in the early detection of the disease and reduce complications. Hence, the objective of this study was to assess the level of knowledge regarding aspects of diabetes among diabetic patients. Methods: The study was conducted using a descriptive cross-sectional research design at Tribhuvan University Teaching Hospital (TUTH). A purposive sampling technique was adopted. Data was collected in 3 months from December 2017 to March 2018 by using a structured questionnaire through interview method among 422 respondents fulfilling the inclusion criteria attending in medical OPD. Analysis was done by descriptive and inferential statistics. Results: The study findings revealed that nearly half of the respondents (43.4%) had moderately adequate knowledge, 36.5% of respondents had adequate and 20.1% had inadequate knowledge on diabetes mellitus. The overall knowledge score was 65.37±SD17.58. Knowledge scores in different aspects of diabetes revealed that respondents had adequate knowledge on diet (79.3%), medicine (78.4%), complications with diabetes mellitus (75.8%) and moderately adequate knowledge was found on the meaning of diabetes (62.5%), exercise (67%), diabetic foot care (52.6%), blood glucose monitoring (53.3%) and follow up visit (75.8%). Diabetic patient’s age (0.026), sex (0.012), education (<0.001), occupation (<0.001), area of residence (0.005) and attended in diabetic counseling (<0.001) were significantly associated with level of knowledge. Conclusion: It is concluded that less than half of the diabetes patients have adequate knowledge on diabetes mellitus and it is associated with age, sex, education, occupation, area of residence and attended diabetic counseling.